Unlocking Local Economic Potential: Understanding the Role of Place-based Industrial Policy in Egypt - Shaban, Nashwa (AUC Knowledge Fountain, 2025)
Industrial Policy has regained prominence in both academic and practical spheres over the years, as the discourse largely shifted from an ideological debate to exploring ways for effective implementation. This renewed interest, coupled with growing concerns over regional inequality and persistent economic distress, has sparked a growing interest in Place-based Industrial Policies. Place-based Industrial Policy is an approach to industrial policy that focuses on both specific industries and locations through various policy Instruments. Similar to industrial policies, the outcomes of place-based policies have been mixed, nevertheless, evidence suggests that they often achieve the intended objectives especially in lagging and declining regions. The relevance of Place-based Industrial Policy in addressing local economic development and regional disparities makes it particularly pertinent for countries in the Global South like Egypt. The main objective of the study is to explore the extent to which Place-based Industrial Policy is adopted in Egypt, while identifying the scope of its applicability. The results of the conducted qualitative research showed that Egypt adopts a fragmented place-based approach to industrial policy, utilizing instruments such as industrial zones, free zones, special tax incentives, and special economic zones. The findings show that there are key challenges to the adoption of place-based industrial policy in Egypt, including overlapping government mandates, weak institutional capacity, and insufficient local data frameworks. In addition, the findings offer unique perspective on how centralization, when guided by input from local stakeholders and the private sector, can serve as an enabler for Industrial Policy. The study highlights the significant potential of place-based industrial policies in Egypt to address regional disparities, leverage local resources, and enhance skill development and infrastructure, warranting further investigation into their impact on Sustainable Development Goals (SDGs) at the local level.